Awareness about developmental coordination disorder - Steenbergen, Bert; Valtr, Ludvík; Dunford, Carolyn; Prunty, Melissa; Bekhuis, Hidde; Temlali, Taha Yassine; van Abswoude, Femke; Lust, Jessica M.; Warlop, Griet; Augustijn, Mireille; Smits-Engelsman, Bouwien C. M.; Wilson, Peter H. (Frontiers in Public Health, 2024)
The present paper is designed to promote awareness of DCD outside the academic world. With a prevalence of 5-6% it is one of the most common disorders of child development (1). It is therefore surprising that so little is known about it among professionals in child healthcare and education (2). Parents have expressed frustration about this lack of awareness, including the general public (3-6). The general aim of this paper was to describe those critical aspects of DCD that will promote awareness.